Real-world performance and accuracy of stress echocardiography: the EVAREST observational multi-centre study. (20th June 2021) - Woodward, William; Dockerill, Cameron; McCourt, Annabelle; Upton, Ross; O'Driscoll, Jamie; Balkhausen, Katrin; Chandrasekaran, Badrinathan; Firoozan, Soroosh; Kardos, Attila; Wong, Kenneth; Woodward, Gary; Sarwar, Rizwan; et al.
Abstract: Aims: Stress echocardiography is widely used to identify obstructive coronary artery disease (CAD). High accuracy is reported in expert hands but is dependent on operator training and image quality. The EVAREST study provides UK-wide data to evaluate real-world performance and accuracy of stress echocardiography. Methods and results: Participants undergoing stress echocardiography for CAD were recruited from 31 hospitals. Participants were followed up through health records which underwent expert adjudication. Cardiac outcome was defined as anatomically or functionally significant stenosis on angiography, revascularization, medical management of ischaemia, acute coronary syndrome, or cardiac-related death within 6 months. A total of 5131 patients (55% male) participated with a median age of 65 years (interquartile range 57–74). 72.9% of studies used dobutamine and 68.5% were contrast studies. Inducible ischaemia was present in 19.3% of scans. Sensitivity and specificity for prediction of a cardiac outcome were 95.4% and 96.0%, respectively, with an accuracy of 95.9%. Sub-group analysis revealed high levels of predictive accuracy across a wide range of patient and protocol sub-groups, with the presence of a resting regional wall motion abnormalitiy significantly reducing the performance of both dobutamine ( P < 0.01) and exercise ( P < 0.05) stress echocardiography. Overall accuracy remained consistently high across all participating hospitals. Conclusion: Stress echocardiography has high accuracy across UK-based hospitals and thus indicates stress echocardiography is being delivered effectively in real-world practice, reinforcing its role as a first-line investigation in the assessment of patients with stable chest pain. Graphical Abstract: